A Survey of Research on Handwritten and Printed Kannada Numeral Recognition Technique - Hallur, Vishweshwarayya C. (Advanced Aspects of Engineering Research Vol. 5, 2021)
Day by day technology is going very fast, digital recognitions are playing wide role and providing more scope to perform research in OCR techniques. Recognition of Kannada handwritten numeral is complicated compared to English and other western numerals. However, many researchers have provided real time solution for printed Kannada numerals. Printed numeral documents recognition still offers many motivating challenges to researchers. Current research offers many solutions on Kannada handwritten documents recognition even then reasonable accuracy and concerning handwritten numeral recognition. Different approaches have been used in each phase of recognition process, whereas each approach provides solution only for few numeral sets.